Antioxidants and Anticholinesterase Activities of the Characterized Ethanolic of Ripe Sesoot (Garcinia picrorrhiza Miq.) Fruit Extract (GpKar) and Xanthone - Sri Utami; Pratami Adityaningsari; Insan Sosiawan; Susi Endrini; Qomariyah Romadhiyani Sachrowardi; Sonny Pamudji Laksono; Said Nafik; Betharie Cendera Arrahmani; Ervi Afifah; Wahyu Widowati (Majalah Obat Tradisional, 2017)
Oxidative stress has been known to contribute to Alzheimer’s disease. Acetylcholinesterase (AChE) enzyme may lead to Alzheimer’s disease as a neurotransmitter. Antioxidants may have protective activities against oxidative damage and Alzheimer’s disease. Acetylcholinesterase inhibitors also can be used in the treatment of various neurological disorders for management of Alzheimer’s disease. This study aimed to determine antioxidant and anticholinesterase effects of Garcinia picrorrhiza Miq. fruit extract (GpKar) and its compounds, xanthone. Antioxidant activity was measured by H2O2 scavenging inhibitory activity, while anticholinesterase activity was measured using modified Ellman method. GpKar has higher H2O2 scavenging inhibitory activity (IC50= 967.28 µg/ml) compared to xanthone (IC50= 1198.95 µg/ml). In the anticholinesterase inhibitory activity, GpKar has lower activity (IC50= 70.25 µg/ml) compared to xanthone (11.80 µg/ml). In summary, GpKar has higher antioxidant activity but lower anticholinesterase activity compared to its compounds, xanthone. However, GpKar has potency as antioxidant agent to prevent Alzheimer’s disease.